Students’ Engagement through Augmented Reality as Learning Media: A Study of Electrical Engineering Students - Maman Suryaman , Dian Budhi Santoso , Fika Natasya Rahma , Risma Fitriani (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
This present paper mainly investigates the implementation of Augmented Reality as Learning Media and Students’ Engagement of the Augmented Reality itself. The purposes of the study are to find out the implementation of AR in electrical engineering course and the level of students’ engagement in using AR technology. Students’ engagement can be divided into behavioral engagement, emotional engagement and cognitive engagement. The data were collected through questionnaire and analyzed then interpreted by using descriptive analysis. The result shows that the use of AR in electrical engineering students is well-implemented as learning media. The students also have positive engagement in behavioral engagement, emotional engagement and cognitive engagement during learning with AR technology as learning media.